Switching cost and cognate facilitation between two signed languages - Adam, Robert; Morford, Jill P. (Frontiers in Language Sciences, 2026)
This study investigated language switching and cognate facilitation in deaf bilinguals fluent in two signed languages—Irish Sign Language (ISL) and British Sign Language (BSL). Ten participants, who were all deaf and were educated in ISL and later exposed to BSL, completed a picture-naming task requiring them to switch between the two languages based on visual cues. The study aimed to establish whether a switching cost—typically observed in unimodal spoken language bilingualism—also exists in unimodal signed language bilingualism, and whether language dominance and cognate status mediated this effect. Results confirmed a general switching cost: participants were slower to respond on switch trials than during a baseline block with no switching. Both language dominance and cognate status affected the switching cost, such that switching costs were greater in the dominant language, and non-cognates were significantly slowed by switching but cognates were not. Accuracy rates were high and did not vary significantly by switching condition or language. As the first investigation to provide evidence of a switching cost in deaf bilinguals who use two signed languages, this study provides an important foundation for future work exploring how language modality and language ecology shape the cognitive control systems underlying language switching.